Pain medicine in fiction. Bekhterev's disease in Evgenii Litvak’s web novel “The Age of Glory and Hope” - Bondarieva, T (Pain medicine, 2022)
The article provides an overview of pain medicine as a component of the art world of fiction. The semantic meaning of the disease (for example, tuberculosis, epilepsy, infectious diseases (plague), Bekhterev's disease) as one of the character's or author's characteristic (Lesya Ukrainka) is analyzed. A general analysis of the integrative connections between medicine and literature as humanities is offered. On the example of the web novel “The Age of Glory and Hope” by Evgenii Litvak, the course of Bekhterev's disease in the main character is reviewed, as well as the therapy proposed by the author in the work as opposed to the conventional medicine. It is noted that the state of pregnancy in which the main character of the novel is, contributes to the intensification of blood supply in the body, which can positively affect recovery. In particular, it is emphasized that in the modern informational space the user has access to special knowledge and professional sources, which allows to operate with specialized medical knowledge (at the erudition level) in the fiction, while being clear to the reader, which is one of the features of internet literature, which includes the web novel “The Age of Glory and Hope” by Evgenii Litvak.